1990
DOI: 10.1148/radiology.177.3.2243982
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stenosis: evaluation with color Doppler flow imaging.

Abstract: Renal artery stenosis (RAS) is the most common correctable cause of hypertension. The current study was undertaken to evaluate the usefulness of color Doppler flow imaging as a screening examination in the detection of significant RAS. Fifty-five kidneys in 30 patients were examined with aortography and color Doppler flow imaging in a double-blind fashion. The peak systolic velocity (PSV) in the renal artery, the renal-aortic ratio (RAR) (ie, the ratio of the PSV in the renal artery to the PSV in the aorta), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(62 citation statements)
references
References 0 publications
2
58
1
1
Order By: Relevance
“…Some investigators report remarkable success, while others have reported dismal results in large unselected patient groups. 15,16 A recent study declared duplex ultrasound to be most valuable not only in the screening for renal artery disease but also to estimate its functional significance by means of determination of the resistive index. 17 The duplex ultrasound performance in this study, however (ie, sensitivity 97%; specificity 98%), was derived from a previous report by the same authors in a selected group of patients with a high prevalence of renovascular disease (58%).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators report remarkable success, while others have reported dismal results in large unselected patient groups. 15,16 A recent study declared duplex ultrasound to be most valuable not only in the screening for renal artery disease but also to estimate its functional significance by means of determination of the resistive index. 17 The duplex ultrasound performance in this study, however (ie, sensitivity 97%; specificity 98%), was derived from a previous report by the same authors in a selected group of patients with a high prevalence of renovascular disease (58%).…”
Section: Discussionmentioning
confidence: 99%
“…Authors, who considered a velocity > 100 cm/s as a parameter, had low accuracy indices, but a high index of inconclusive examinations, denoting individual technical limitations in the study of the renal arteries on vascular color Doppler ultrasound 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Experienced operators can achieve sensitivities of up to 95% for the detection of RAS (24). However, US is very operator dependent and has, therefore, a relatively high interobserver variability and a low sensitivity when performed by a nonexperienced operator (25,26). Additionally, it often fails in obese patients or those with bloated small or large bowl.…”
Section: Current Position: Indications For Imaging and Imaging Technimentioning
confidence: 99%